The raven and the loon - Qitsualik-Tinsley, Rachel, 1953-; Qitsualik-Tinsley, Sean, 1969- (Inhabit Media Inc., 2013)
In the time before animals were as they are today, Raven and Loon were both white. Their feathers had no colour at all. Raven spent his days swooping through the sky trying to fight off his incessant boredom, while loon spent her days in her iglu working away on her sewing. One day, too bored to even fly, Raven visited Loon and suggested a sewing game that would give their feathers some much-needed colour. The results--not at all what the two birds expected--led to Raven and Loon acquiring their now-familiar coats.